The Image of Imam Ali (A.S) in Persian Language and Literature - Talebzadeh, Sakineh; Mohammad Beigi, Shahrokh (LANGUAGE ART, 2020)
Among the infallibles (A.S), the high and heavenly personality of Imam Ali (A.S) has had a profound effect on the souls and lives of noble and righteous people; because the spiritual and personality dimension of this Imam is beyond time and place. In the meantime, traditional and modern poets and writers have had the most enjoyment of this effect and have left their love and affection in the form of original poems and prose. In the article, first this issue is addressed among both groups of poets, then in a library research and based on the technique of describing and analyzing the content, an attempt is made to address some of the recurring themes in Persian poetry and literature about the pious master. This study shows the personality of the Mawla-ye Mottaqian (A.S), behavioral and internal characteristics, temperament, some important historical events of his life, his blessed birth, Ghadir Khumm, Laylat al-Mabīt, their relationship with the Prophet, their position in the Qur'an, their martyrdom and ... is one of the most important themes that is more prominent in the poetry of poets.